(untitled) (Revista Brasileira Multidisciplinar, 2015)
In the modern world, modern culture has given rise to consumption culture, in which the ownership of goods and objects becomes a language through which the entire society communicates and talks. In modern consumption cultures, the goods are composed of a large number of objects highly differentiated in terms of scarcity and of cost, so that there is always a higher level of consumption to which people can aspire. This article used bibliometrics to quantify and to identify the methodologies used in 56 papers on culture and consumption presented to ENANPADs from 2009 to 2012. Data were collected electronically and analyzed using descriptive statistical methods. The greatest part of the papers were considered ethnographic exploratory qualitative research or netnographic, using the interview for the raising of evidences, which were treated by the technique of discourse analysis. The most relevant conclusions are that the authors are not always concerned about giving this information to their readers, that theoretical research remains unattractive to researchers, and that they reject the use of less common techniques when analyzing qualitative data.